Integration of Deep Learning in the Independent Curriculum: Implementation Strategies and Their Impact - R, Nurmala; Achmad Zultan Mansur; Jusmawati (International journal of technology and education research, 2025)
The global demand for 21st-century competencies necessitates a radical transformation in education. Indonesia responded with the Independent Curriculum, aiming to form the Pancasila Student Profile. However, there is a gap in implementation models and empirical data on the integration of Deep Learning within the Independent Curriculum context. This study uses a Systematic Literature Review (SLR) to analyze DL's implementation strategy and its impact on student competence. The findings confirm a strong synergy, showing Deep Learning is a holistic pedagogical strategy based on three pillars: Mindful, Meaningful, and Joyful. Deep Learning integration, facilitated by Project-Based Learning, significantly improves students' knowledge transfer capability and strengthens non-cognitive competencies like Critical Reasoning and Collaboration. The study concludes that Deep Learning is an essential and transformative strategy for Independent Curriculum, but requires systemic commitment to enhance teacher capacity and ensure policy coherence.